Ecological Virtue: Articulating Tolerance as a Mutual-Respect Between Human Being and Environment - Muhammad Nur Prabowo Setyabudi (International Journal of Interreligious and Intercultural Studies, 2020)
This paper elaborates the meaning of eco-tolerance in the context of ecological community between human and environment. Tolerance is often discussed as theological conception related to the relationship between religion (religious virtue) or socio-political conception related to the relationship between community or identity (political virtue). But how to build a tolerant relationship between human and their environment? What kind of wisdom that we need? I discuss about tolerance as an ecological wisdom or, â€œecological virtueâ€, and a need for human to become a moral subject who has an ecological insight. I will elaborate ethical arguments from the perspective of virtue ethics, one of important disciplines in normative ethics, and environmental ethics, the most important branch in applied ethics, which describe that humans really need to have a mindset of ecocentric oriented, be wise and respectful toward the nature and the environment, build a mutual respect relationship, tolerance is not only a main value in political community, but also a main value in ecological community in a mutual respect ecosystem atmosphere and the existence of mutual recognition between human and nature.